STRENGTHENING LAND REGISTRATION SYSTEM THROUGH IMPLEMENTATION OF DOMAIN APPROACH IN MANIFESTING LEGAL CERTAINTY AND COMMUNITY JUSTICE - Kurniati, Nia; Mordekhai, Jordan (Universitas Padjadjaran, 2021)
As an implementation of welfare society, the government issued Law Number 5 of 1960 Article 19 paragraph (2) c, which provide the legal certainty of land rights for all Indonesians carried out through land registration. The land registration system adopted by Indonesia is negative land cadastre with positive tendency. The implementation of land registration provide the basis of state duty to produce land registration evidence, namely certificate, which is valid as a strong proof of rights. This certificate guarantees the correctness of physical data besides juridical data as long as it is not proven otherwise. Method: This legal research used Normative juridical method, with qualitative juridical data analysis. Results of the study: Negative land cadastre with positive tendency adopted by Indonesia currently does not guarantee legal certainty of land ownership and the community justice itself. This is indicated by the fact that there is still a phenomenon of land disputes, among the result of the issuance of overlapping. By using a legal cadastre-based domain approach, through an approach of extracting historical values of land and integrating the process of dialogue within the issuing of certificate; obtaining legal certainty and the community justice can be achieved. Conclusion: Negative land cadastre with positive tendency is still unable to manifest legal certainty of land ownership and community justice so it is appropriate that an adage states “the highest legal certainty, is the highest injustice”. Strengthening land registration system through the domain approach is an alternative option to manifest legal certainty and community justice.